177k views
4 votes
6x-1=-3x-4+2x-5 steps?

2 Answers

5 votes
Step 1: combine like terms. The -3x and 2x can be combined, and the -4 and -5 can be combined, giving
6x-1 = -x -9

Step 2: move x’s to one side. Get rid of the -x on the right by adding x to both sides, giving
5x-1 = -9

Step 3: move numbers to opposite side. Add one to both sides
5x = -8

Step 4: isolate x. Divide both sides by 5
So, x = -8/5

You can plug this back in to the original equation to see if I️t works.
User RedXIII
by
6.0k points
0 votes
Let’s simplify the right side first
6x-1 = -x - 9
Add x to both sides and add 1 to both sides
7x = 8
x = 8/7
Hope this helps!
User Keith Walton
by
5.6k points